The illegal transboundary movement of waste: an economic analysis of a transnational environmental crime - Camilla Bignotti (Lexambiente, 2020)
This paper deals with the problem of the illegal transboundary movement of waste and the related dirty collar crimes committed by the transnational organized crime groups. The objective is to conduct an economic analysis of the law to determine if the sanctions imposed by the European States are capable of contrasting the phenomenon.